How Islamic work ethics affect thriving at work and employee commitment - Gustiawan, Deni; Azzahra, Reynia Shifa (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2024)
This study explores the relationship between Islamic Work Ethics (IWE) and organizational commitment (COM), with thriving at work (THR) as a mediating factor. Data were collected from 172 employees across various sectors in Jakarta and analyzed using Structural Equation Modeling (SEM) with the JAMOVI program. The findings reveal that while there is no direct relationship between IWE and organizational commitment, thriving at work fully mediates this relationship, highlighting the importance of fostering vitality and growth in the workplace. Furthermore, gender-specific analysis shows that the relationships among IWE, thriving, and commitment are significant only for female employees. This study contributes to the literature by uncovering the mediating role of thriving at work in the IWE-commitment relationship, a perspective underexplored in prior research. It also offers new insights into how gender influences the impact of Islamic work ethics on workplace outcomes, providing a nuanced understanding of these dynamics. Public Interest Statement The gender-specific findings further emphasize the importance of tailoring strategies to address men's and women's unique needs, ensuring a more equitable and supportive workplace for all.